A Proposed Concept for a Teaching Strategy Based on the Schwartz Model to Develop Syntactic (Nahwi) Thinking Skills Among Secondary School Female Students - Al-Huzali, Khadijah Atiah Falih (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to present a proposed concept for a teaching strategy based on the Schwartz Model, with the goal of developing Syntactic (Nahwi) thinking skills among secondary school female students. Additionally, the study sought to create a comprehensive list of Syntactic (Nahwi) thinking skills that are suitable for this purpose. To achieve these objectives, the researcher adopted a descriptive approach and developed a list of Syntactic (Nahwi) thinking skills, consisting of 23 sub-skills divided into six main categories: classification, inference, reasoning, interpretation, analysis, and evaluation. This list was used as the basis for constructing the proposed teaching strategy, which was applied to Unit 2 of the Linguistic Competencies course for first- year secondary students, focusing on the topic of the "genitive complements" (the genitive case with a preposition (al-jar biharf al-jar) and the genitive case with addition (al-jar bil-idafah)) in order to develop the students’ Syntactic (Nahwi) thinking skills for secondary school female students. The results of the study showed the final list of appropriate Syntactic (Nahwi) thinking skills for the female students, and it proposed a suggested teaching strategy based on the Schwartz model to achieve these skills. This included the conceptual foundations (philosophy), general objectives, implementation procedures in the content, requirements for execution, potential obstacles with proposed solutions based on the results. The study provided a set of recommendations and suggestions to enhance the teaching of Syntactic (Nahwi) thinking skills.